Integrating human behaviour dynamics into flood disaster risk assessment - Aerts, J; Botzen, W; Clarke, K; Cutter, S; Hall, J; Merz, B; Michel-Kerjan, E; Mysiak, J; Surminski, S; Kunreuther, H; Hall, J (Nature Publishing Group, 2018)
The behaviour of individuals, businesses, and government entities before, during, and immediately after a disaster can dramatically affect the impact and recovery time. However, existing risk-assessment methods rarely include this critical factor. In this Perspective, we show why this is a concern, and demonstrate that although initial efforts have inevitably represented human behaviour in limited terms, innovations in flood-risk assessment that integrate societal behaviour and behavioural adaptation dynamics into such quantifications may lead to more accurate characterization of risks and improved assessment of the effectiveness of risk-management strategies and investments. Such multidisciplinary approaches can inform flood-risk management policy development.